Dampak Program Bina Desa Terhadap Perilaku Masyarakat di Desa Binaan - Rilus A Kinseng; Iis Diatin; Achmad Fahrudin (Buletin Ekonomi Perikanan, 1996)
Since 1992, every forest consession holder has been obliged to carry out a special program in a village or villages in or arround the concession. Bassically, the purpose of the program is to change behavior of the villagers, such as abondaning the practice of shifting cultivation, developing awarness on environment, etc.The main objective of this study is to investigate impacts of the program on the behavior of the villagers in the village where the program has been carried out. This would include agricultural practices and attitude as we/I as way of thinking of the villagers. The later consists of nine dimensions: (a) attitude toward education, (b) universalism, (c) openess, (d) rationality, (e) value orientation, (f) gender, (g) family planning, (h) environmental awarness and (I) farming orientation.The method used in this study was Natural Experiment (Babbie, 1989 : 230). Several component of the behavior were quantified using scoring system.This study reveals that in the domain of the agricutural practices, a quite fundamental change has taken place, that is the switching of the agricultural practices from swidden agriculture to the ·permanent cultivation" system. There is a .significant difference at the level of 95 % in the seven component: attitude toward education, universalism, openess, rationality, value orientation, environmental awarness and the farming orientation. There is no siginficant difference in the gender and family planning issues.